Piecewise-smooth+ version of the implicit-function theorem - Miklyukov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We introduce a class of piecewise-smooth + mappings and prove the implicit-function theorem for this class. The proof is based on the theorem on global homeomorphism, which follows from the well-known Chernavskii theorem.